(untitled) (Research, Society and Development, 2021)
Introduction: In Brazil, the prevalence of overweight and obesity is higher among individuals with less education, 24.5% of obesity among those with 0 to 8 years of schooling and 15.8% in the group with 12 years or more education. Objective: the objective of this study was to analyze the association between the socioeconomic profile and the nutritional status of overweight adults in the municipality of Paranavaí - PR. Method: This is a descriptive cross-sectional study designed to identify the factors associated with nutritional status: level of income and education; in adults, of both sexes, aged between 18 and 50 years, with excess weight. Results: Among the 147 participants, the average age presented was 34.52 years old. 87 were married, 54 single, 5 divorced and 1 widower, with regard to sex 119 were women, most had 8 or more years of study, participants prevailed. with Grade I Obesity with 32.65%. Conclusion: The nurse as a manager of a basic health unit has a fundamental role in the development of health education activities aimed at changing the lifestyle for the prevention and treatment of obesity.